Revolutionary Waves: A Comparative Exploration of Political Leadership and Governance during French Revolution and in Present-Day Pakistan - Muhammad Younus; Hajira Gul; Abdul Rehman; Ibrahim Shah (International Journal of Scientific Multidisciplinary Research, 2023)
This academic article compares political leadership and governance between the French Revolution to contemporary Pakistan, a nation facing political issues. This study examines the historical revolutionary waves that swept France in the latter part of the 18th century and Pakistan's political dynamics to reveal the similarities and differences in authority and governance. We aim to illuminate the reasons that led to the rise of French Revolution leaders by analyzing a wide range of historical records, primary sources, and contemporary literature. We want to understand how these leaders' views and deeds shaped history. This analysis compares Pakistan's political scene and leaders' leadership styles. We will also examine these leaders' issues and their impact on governance and socioeconomic development. The analysis shows revolutionary fervor in both periods. These leaders inspired and mobilized the public. Our extensive research also shows significant differences in ideology, power consolidation strategies, and governance systems during the distinct times—this study illuminates leadership and governance's long-term effects. We can learn from history. This research contributes to understanding political leadership, governance, and societal results